Pengujian Kesuksesan Implementasi Sistem Informasi Akuntansi pada Usaha Kecil Menengah dengan Model Adaptasi Delone & McLean - Adiba Muthia Nurhaida; Wahyu Manuhara Putra (Universitas Muhammadiyah Yogyakarta, 2019)
This study is based on the importance of the role of accounting information software in Small and Medium Enterprises. This study examines the success of the implementation of accounting information systems in small and medium enterprises with adaptation models of DeLone and McLean. The object of this study is small and medium enterprises in Yogyakarta. This study uses a quantitative method using a questionnaire. The study sample was taken using the Convenience sampling method. The analysis technique uses the updated DeLone and Mclean information system success model (2003). The tool used is SmartPLS 3.0. The results showed that the quality of the system proved to have no effect on the use of accounting information systems, system quality proved to have no effect on user satisfaction, information quality proved to have a positive effect on usage, information quality proved to have a positive effect on user satisfaction, service quality proved to positively influence usage, quality service proved to have a positive effect on user satisfaction, use proved to have a positive effect on net benefits, user satisfaction proved to have no positive effect on net benefits.